2022
DOI: 10.7554/elife.81704
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the GOLD-domain seven-transmembrane helix protein family member TMEM87A

Abstract: TMEM87s are eukaryotic transmembrane proteins with two members (TMEM87A and TMEM87B) in humans. TMEM87s have proposed roles in protein transport to and from the Golgi, as mechanosensitive ion channels, and in developmental signaling. TMEM87 disruption has been implicated in cancers and developmental disorders. To better understand TMEM87 structure and function, we determined a cryo-EM structure of human TMEM87A in lipid nanodiscs. TMEM87A consists of a Golgi-dynamics (GOLD) domain atop a membrane spanning seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 65 publications
3
10
3
Order By: Relevance
“…Human TMEM87A (hTMEM87A) and its homolog hTMEM87B, members of the Lung Seven Transmembrane Receptor (LUSTR) family 1 , are mainly present within Golgi. hTMEM87A is proposed to have a role in endosome-to-Trans Golgi Network (TGN) retrograde transport 2,5 which is also supported by its structural similarity with the Wnt transporter protein, Wntless 15 . However, a fraction of hTMEM87A localizes to the plasma membrane in cancer cells such as melanoma and glioblastoma multiforme (GBM), where it is associated with mechanosensitive cation channel activity 4,16 .…”
Section: Main Textmentioning
confidence: 97%
See 1 more Smart Citation
“…Human TMEM87A (hTMEM87A) and its homolog hTMEM87B, members of the Lung Seven Transmembrane Receptor (LUSTR) family 1 , are mainly present within Golgi. hTMEM87A is proposed to have a role in endosome-to-Trans Golgi Network (TGN) retrograde transport 2,5 which is also supported by its structural similarity with the Wnt transporter protein, Wntless 15 . However, a fraction of hTMEM87A localizes to the plasma membrane in cancer cells such as melanoma and glioblastoma multiforme (GBM), where it is associated with mechanosensitive cation channel activity 4,16 .…”
Section: Main Textmentioning
confidence: 97%
“…In this work, we determined the high-resolution cryo-EM structures of hTMEM87A in complex with the Golgi membrane phospholipid PE and the pharmacological inhibitor gluconate. Because the domain arrangement of hTMEM87A closely resembles that of Wntless, a regulator of Wnt protein sorting and secretion, and other GOLD domain seven-transmembrane helix (GOST) proteins 15 , the most parsimonious conclusion is that hTMEM87A is involved in the trafficking, secretion, and sorting of yet unidentified proteins. While future studies will be required to examine its function, our structure analysis of hTMEM87A, complemented by MD simulations and electrophysiological analysis, provide crucial insights into mechanistic aspects of hTMEM87A as a non-selective voltage-gated cation channel.…”
Section: Role Of Phosphatidylethanolamine and Tm3 In Ion Conduction O...mentioning
confidence: 99%
“…However, it has not been determined whether TMEM87A is an ion channel or not. Indeed, TMEM87A has been recently proposed as either a pore-forming or auxiliary subunit for a mechanosensitive ion channel 24 , which has been immediately contradicted by the lack of mechanosensitive channel activities in TMEM87A reconstituted proteoliposome 25 .…”
Section: Mainmentioning
confidence: 99%
“…It was thus renamed Elkin1, from the Greek word Elko ("to pull"). The cryo-EM structure of human TMEM87A published recently (Hoel et al , 2022) shows that TMEM87A is a monomer with a sandwich-like extracellular domain and a transmembrane domain of 7 TMs (Fig. S10).…”
Section: Tmem87a Mechanosensitive Channel Component or Trafficking Ch...mentioning
confidence: 99%
“…S10). Ion-conducting pore cannot be identified from the structure, and the authors also failed to record mechanosensitive currents from TMEM87A reconstituted proteoliposomes (Hoel et al , 2022). Further structural analyses revealed that TMEM87A is neither a G protein-coupled receptor, but shares similarity with several Golgi-dynamics (GOLD) domain seven-transmembrane helix (GOST) proteins that function in membrane-associated protein trafficking.…”
Section: Tmem87a Mechanosensitive Channel Component or Trafficking Ch...mentioning
confidence: 99%